The Chinese Madhyama Agama and The Pali Majjhima Nikaya —A comparative study - Venkatakrishna, B V (Journal of Dharma, 1992)
Bhikshu Thich Minch Chau, The Chinese Madhyama Agama and The Pali Majjhima Nikaya —A comparative study. Delhi : Motilal Banarasidas, 1991, Pp. 388.